POTENSI KULIT KOPI DAN KULIT KETELA SEBAGAI ADITIF PADA PEMBUATAN SILASE RUMPUT GAJAH (Pennisetum purpureum) (Potential of Coffe and Cassava Peel as Additive For Making An Elephant Grass (Pennisetum purpureum) Silage) - Daryatmo, Joko; Arifin, Zainal; L. Ledoh, Dominggus (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2018)
The study was conducted to determine the effect of the use of coffe and cassava peel to the organoleptic of elephant grass silage. The study was conducted using a completely randomized design (CRD) consisting of 3 treatment are: P0 (Elephant grass (Pennisetum purpureum) 100%) as a control, P1 (elephant grass+coffe peel), P2 (elephant grass+cassava peel, with 3 replications. The variables measured were: color, odor, pH, texture and physical condition. The results showed that treatment P2 (elephantgrass+cassava peel) is the best composition to produce silage based on the observation of the organoleptic and physical conditions of the silage.Keywords: Coffe peel, Cassava peel, Silage, Pennisetum purpureum